Pengukuran Kepuasan Pengguna Situs Web Dengan Metode End User Computing Satisfaction (EUCS) - Ahmad Fitriansyah; Ibnu Harris (Query: Journal of Information Systems, 2018)
This research conducted to determine the level of user satisfaction of Universal University website so that the website administrator can get an overview of the level of user satisfaction as well as future evaluation materials. Measurement of user satisfaction used End User Computing Satisfaction (EUCS) method. Measure of user satisfaction are two methods, End User Computing Satisfaction (EUCS) and User Information Satisfaction (UIS). Based on the research of Seddon & Yip [4] who conducted a comparison between the EUCS and UIS methods it was found that the EUCS method was more useful than the UIS method. The variables in this research are content, accuracy, format, ease of use, and timeliness. The samples in this study collected from 168 respondents consisting of 3 staffs, 17 lecturers and 148 students. The data collection used a closed questionnaire consisting of 13 question for the five variables being studied. From the data obtained, concluded that the overall level of user satisfaction is in the average value of 2.64 at level 3 (neutral), which means that according to the general respondents’ perception, Universal University website not said satisfactory but also not disappointing. Variables that have assessed as good enough are accuracy and ease of use, while for content, format, and timeliness are still considered for more improvement and developed again. Keywords: user, satisfaction, eucs, website